The Islamic worldview for medical professions - Shogar, Ibrahim Adam Ahmed (2017)
Implications of the word view on thought (at individual level) 1.It gives meaning and purpose to our life. 2.Provides the systematic answers to the ultimate / cosmic questions; 3.Interprets the being as whole and identifies between means and goals; 4.Gives meaning to human life and establishes ethical commitment; 5.Identify role of human being in relation to other creatures; 6.Establishes the theoretical principles for practical way of life; B.Implications of the word view on life (at individual & collective levels) 1.Creates the essences of unity and harmony in community; 2.Identifies the different communities and civilizations; 3.Establishes the basic principles of social order and rules for living, with regard to how to satisfy the basic human needs; 4.Protects the community from disintegration.